Encounters with American ethnic cultures - Kilbride, Philip Leroy; Goodale, Jane C. (Jane Carter), 1926-2008; Ameisen, Elizabeth R. (University of Alabama Press, 1990)
Encounters with American Ethnic Cultures represents a cultural approach to understanding ethnic diversity in the Philadelphia metropolitan area. Thirteen chapters, each using an ethnographic field methodology, explore such ethnic experience as the "invisible" (WASPS and African-Americans); "self-chosen" (Welsh-American, Irish-American, and Ukrainian-American); "gender-related" (the Lubovitcher); "religious" (Jewish, Native American, Greek-American, and Puerto Rican); and "dislocated" (Cambodians and the homeless). Ethnographic fieldwork focuses an insider's view on the meaning of ethnic ex